Clarity of responsibility, accountability, and corruption - Schwindt-Bayer, Leslie A. (Cambridge University Press, 2017)
Machine generated contents note: 1. Introduction; 2. A clarity of responsibility theory of corruption; 3. A dataset of democracy and corruption; 4. Clarity of responsibility and aggregate corruption perceptions; 5. Corruption voting - a survey analysis; 6. Corruption and accountability - an experimental analysis; 7. The effect of clarity on elite efforts to combat corruption; 8. Beyond anticorruption efforts - elite attention to corruption; 9. Conclusions